Low-dose mivacurium facilitates laryngeal mask airway insertion in patients undergoing hysteroscopic surgery: a prospective, single-center, double-blind randomized controlled trial - Guan, Yingchao; Wu, Lizhen; Wang, Haochen; Wang, Conghui; Lin, Yusong; Ju, Minghong; Cong, Xiaojing; He, Wen; Wang, Xiaodong (Frontiers in Pharmacology, 2025)
BackgroundTo explore whether the application of mivacurium can facilitate laryngeal mask airway (LMA) insertion and benefit patients.MethodsA total of 167 patients undergoing hysteroscopy were randomly divided into mivacurium (group M) and control (group C) groups. The anesthesia induction scheme was mivacurium + sufentanil + propofol in group M, whereas mivacurium was replaced with saline in group C. The main outcome was the LMA insertion condition Secondary outcomes included attempts and elapsed time of LMA insertion, intraoperative anesthetic consumption, perioperative hemodynamics, postoperative sore throat (POST), nausea, vomiting, dizziness, and agitation.ResultsThere was no difference in the baseline data (p > 0.05). There was no significant difference in mouth opening; however, the incidence of swallowing, coughing, body movement, and pharyngeal spasm in group M was lower (p < 0.001), and the proportion of no resistance during LMA insertion was higher (80.5% vs. 21.2%, p < 0.001). The success rate of first-attempt LMA insertion in group M was higher (98.8% vs. 48.2%, p < 0.001), the elapsed time was shorter (16.9 (9.0) vs. 73.0 (91.5) s, p < 0.001), and fewer patients needed additional propofol (1.2% vs. 54.1%, p < 0.001). Blood staining on the LMA surface showed no significant difference, but the postoperative pharyngeal pain score in group M was lower (1.0 (1.0) vs. 2.0 (1.0), p < 0.001). Intraoperative propofol and remifentanil consumption, postoperative dizziness and nausea were lower in group M.ConclusionMivacurium facilitates LMA insertion and reduce intraoperative anesthetic consumption and adverse reactions, such as POST, nausea, and dizziness,so as to benefit the patient.Clinical Trial Registrationclinicaltrials.gov, identifier ChiCTR2500101122.